(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The current study at Seshadripuram First Grade College focuses on postgraduate students’ perceptions of library staff behaviour. Data collected from the students through a questionnaire was used for this purpose. Overall, 78 respondents gave their opinions in the survey and more than 50 per cent of students said that they were extremely happy with the services provided by the library and the professionals’ behaviour. It demonstrates that one of the major elements in boosting library traffic is behaviour.